In-vivo high-speed biomechanical imaging of the cornea using Corvis ST and digital image correlation. (February 2023) - Wang, Bo; Yang, Lanting; Cheng, Jiaxuan; Wang, Junjie; Mei, Yue
Abstract: In-vivo corneal biomechanical characterization has gained significant clinical relevance in ophthalmology, especially in the early diagnosis of eye disorders and diseases (e.g. keratoconus). In clinical medicine, the air-puff-based tonometers such as Ocular Response Analyzer (ORA) and Corvis ST have been used in the in-vivo biomechanical testing. In the test, the high-speed dynamic deformation of the cornea under air-puff excitation is analyzed to identify the abnormities in the morphological and biomechanical properties of the cornea. While most existing measurements reflect the overall corneal biomechanical properties, in-vivo high-speed strain and strain rate fields at the tissue level have not been assessed. In this study, 20 subjects were classified into two different groups: the normal (NORM, N = 10) group and the keratoconus (KC, N = 10) group. Image sequences of the horizontal cross-section of the human cornea under air puff were captured by the Corvis ST tonometer. The macroscale mechanical response of the cornea was determined through image analysis. The high-speed evolution of full-field corneal displacement, strain, velocity, and strain rate was reconstructed using the incremental digital image correlation (DIC) approach. Differences in the parameters between the NORM and KC groups were statistically analyzed and compared. Statistical results indicated that compared with the NORM group, the KC corneas absorbed more energy (KC: 8.98 ± 2.76 mN mm; NORM: 4.79 ± 0.62 mN mm; p-value <0.001) with smaller tangent stiffness (KC: 22.49 ± 2.62 mN/mm; NORM: 24.52 ± 3.20 mN/mm; p-value = 0.15) and larger maximum deflection (KC: 0.99 ± 0.07 mN/mm; NORM: 0.92 ± 0.06 mN/mm; p-value <0.05) on the macro scale. Further, we also observed that The maximum displacement (KC: 1.17 ± 0.06 mm; NORM: 1.06 ± 0.07 mm; p-value <0.005), velocity (KC: 236 ± 29 mm/s; NORM: 203 ± 17 mm/s; p-value <0.01), shear strain (KC: 24.43 ± 2.59%; NORM: 20.26 ± 1.54%; p-value <0.001), and shear strain rate (KC: 69.74 ± 11.99 s −1 ; NORM: 54.84 ± 3.03 s −1 ; p-value <0.005) in the KC group significantly increased at the tissue level. This is the first time that the incremental DIC method was applied to the in-vivo high-speed corneal deformation measurement in combination with the Corvis ST tonometer. Through the image registration using incremental DIC analysis, spatiotemporal dynamic strain/strain rate maps of the cornea can be estimated at the tissue level. This is constructive for the clinical recognition and diagnosis of keratoconus at a more underlying level. Highlights: DIC method was combined with the Corvis ST tonometer for the first time. In-vivo high-speed full-field corneal deformation under air-puff was analyzed. Structural and biomechanical properties between NORM and KC corneas were compared. KC corneas show significantly larger shear strain and shear strain rate than NORM. DIC measurement is more sensitive to local histopathological changes in KC corneas.